2010
DOI: 10.1159/000301915
|View full text |Cite
|
Sign up to set email alerts
|

Papuloerythroderma 2009: Two New Cases and Systematic Review of the Worldwide Literature 25 Years after Its Identification by Ofuji et al.

Abstract: Background: Even after the description of papuloerythroderma of Ofuji (PEO) in 1984, little is known about this clinical entity. Objective:To report on 2 new cases of PEO and review of the worldwide literature on this topic. Methods: Article citations were searched on several biomedical search engines (PubMed, EMBASE, SCOPUS, Google Scholar). Papers were retrieved either online or in print. Results: A grand total of 170 PEO cases were identified. Most patients were older than 55 years and of Asian or white des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 127 publications
5
100
1
2
Order By: Relevance
“…Torchia et al [3] recently reviewed the worldwide literature on PEO for the 25 years since its identification by Ofuji et al [1] and reported that associated malignancies were found in 37 (21.8%) of 170 cases. However, they commented that the data probably reflect overreporting, because, in several instances, the association between PEO and a given cancer was the main reason for publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Torchia et al [3] recently reviewed the worldwide literature on PEO for the 25 years since its identification by Ofuji et al [1] and reported that associated malignancies were found in 37 (21.8%) of 170 cases. However, they commented that the data probably reflect overreporting, because, in several instances, the association between PEO and a given cancer was the main reason for publication.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was based on the diagnostic criteria for PEO described by Torchia et al [3], which includes an erythroderma-like eruption formed by the coalescence of flat-topped, red-to-brown papules with a cobblestone-like appearance, the deck chair sign, itch and histopathological exclusion of cutaneous T cell lymphoma. The standard screening investigations included full blood count, renal and liver function tests, serum IgE levels, some tumor markers, urinalysis and stool examinations.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major criteria for PEO are as follows: (i) erythroderma‐like eruptions formed by coalescence of flat‐topped, red‐to‐brown papules with cobblestone‐like appearance; (ii) itch; (iii) deck‐chair sign; (iv) histopathological exclusion of other skin diseases; and (v) absence of causative factors 4. Because the present case showed no characteristic papular eruptions, the criteria were not fulfilled.…”
Section: Figurementioning
confidence: 89%
“…В доступной нам отече-ственной литературе случаев описания ПО мы не встретили. По имеющимся данным [2,3], большин-ство больных этим заболеванием являются лицами азиатского происхождения. Однако в последние го-ды случаи ПО отмечаются и среди европейцев [4,5].…”
unclassified